Association between different composite dietary antioxidant indexes and constipation in American male adults: a cross-sectional study - Sun, Wei; Wang, Yuchao; Han, Lu; Liu, Yinshi; Liu, Hongru; Tong, Yunbing; Jiang, Ziying; Xu, Chen; Sun, Daqing (Frontiers in Nutrition, 2024)
Background: Oxidative stress is acknowledged as a pivotal factor in the intricate pathophysiological processes and pathogenesis of constipation. Modifying dietary patterns can elevate in vivo antioxidant biomarker levels, consequently mitigating oxidative stress. The Composite Dietary Antioxidant Index (CDAI) provides a dependable scoring mechanism for quantifying the potential antioxidant capacity of diets. The association between CDAI levels and the risk of constipation remains uncertain.Purpose: To investigate the potential correlation between CDAI and constipation, aiming to improve constipation management through dietary guidance.Methods: A total of 11,165 adults aged ≥20 years, drawn from the 2005-2010 National Health and Nutrition Examination Survey, were enrolled in this cross-sectional study. We evaluated the correlation between CDAI levels and the risk of constipation through three weighted logistic regression models. Restricted cubic spline (RCS) analysis was employed to assess nonlinear trends, and stratified analyses were conducted.After adjusting for all confounding variables, the findings revealed an association between CDAI and constipation (OR=0.937; 95% CI [0.892, 0.984], p=0.012). Moreover, individuals in the highest quartile of CDAI demonstrated a 40.1% lower likelihood of experiencing constipation compared to those in the lowest quartile (OR=0.599; 95% CI [0.382, 0.939], p=0.027). The RCS analysis indicated a linear relationship between CDAI and constipation (P-non-linear =0.1016). Subgroup analysis by gender revealed a negative correlation in the male population (OR=0.871; 95% CI [0.801, 0.947], p=0.002), with men in the highest CDAI quartile exhibiting a 59.8% lower likelihood of experiencing constipation compared to those in the lowest quartile (OR=0.402; 95% CI [0.206, 0.787], p=0.010). Furthermore, alterations in selenium (OR=0.997; 95% CI [0.995, 1.000], p=0.039) per milligram were independently linked to constipation. In a gender subgroup analysis of a single antioxidant, changes per milligram of vitamin E (OR=0.904; 95% CI [0.838 to 0.975], P=0.011) among males were independently associated with constipation.The fully adjusted model showed a correlation between CDAI and constipation and a significant correlation in quartiles. Meanwhile, subgroup analysis by gender showed that CDAI was negatively associated with constipation in the male population. Moreover, the findings of this study imply that investigations into antioxidant diets should be contextualized within dietary patterns.